PENGGUNAAN KUASA MENJUAL DIDALAM PERALIHAN HAK MILIK ATAS TANAH MELALUI JUAL-BELI - Adnyana, Adnyana (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2015)
The authorization pursuant to Article 1792 of the Civil Code is "an agreement by which a given authority to another person, who received it, for conducting an affair on his behalf". It seems clear on the one hand there is the so-called to give and some are called to receive power, each party both receiver and giver have equal rights and obligations in running the power.  In a very rapid growth dynamics can be found in the deed of transfer of power that the land ownership through purchase, clauses can not be withdrawn or disregard of Article 1813 of the Civil Code which is referred to as "Power of Absolute", it means no longer balanced and adverse the power giver if concerned about the rights and obligations of the giver and the receiver of power.  In connection with the absolute power of the transformation of property rights to land through purchase, there are some legislation that expressly rohibits:  Instruction of the Minister of Home Affairs No. 14 of 1982 on the Prohibition of Use of Absolute Powerful As the transfer of Land Rights,  Government Regulation No. 24 of 1997 on Land Registration, in  Article 39 paragraph (1) letter d.,  Supreme Court Decision No. 2584 / K / Pdt / 1986 explicitly states that "absolute power of attorney regarding the sale and purchase of land can not be justified because in practice often misused for smuggling and selling land",  Decision of the Supreme Court Reg. No. 2817 / K / Pdt / 1994 explicitly states that "buying and selling is done on the basis of absolute power is invalid and void".  As a result of the ban, the use of absolute power in the transfer of property rights through the purchase can not be done because it is illegal and null and void.
Keywords: power to sell; transfer of property rights; land transfer